The Analysis Of Effectiveness Of Student Learning Outcomes Improvement Using The Nht (Number Head Together) Learning Model - Edward Gland Tetelepta; Ferdinand Salomo Leuwol; Saparuddin Rambe; David Ranlyns Efraim Selan; Antonius Rino Vanchapo (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study is a quantitative, quasi-experimental investigation into how the Number Head Together learning approach affects students' learning outcomes. A class V student population and a